Bad moms [videorecording (DVD)] - Lucas, Jon, 1976-; Lucas, Jon, 1976-; Kunis, Mila, 1983-; Hahn, Kathryn, 1974-; Bell, Kristen, 1980-; Smith, Jada Pinkett, 1971-; Applegate, Christina, 1971- (Universal Pictures Home Entertainment, 2016)
" ... A women's shared, near orgiastic pleasure in their freedom and friendship."--New York Times.